A new genus and species for the first recorded cave-dwelling Cavernicola (Platyhelminthes) from South America - Ana Leal-Zanchet; Stella Souza; Rodrigo Ferreira (ZooKeys, 2014)
Species diversity of Brazilian cave fauna has been seriously underestimated. A karst area located in Felipe Guerra, northeastern Brazil, which is a hotspot of subterranean diversity in Brazil, has revealed more than 20 troglobitic species, most of them still undescribed. Based on recent samplings in this karst area, we document the occurrence of the suborder Cavernicola (Platyhelminthes) in South American hypogean environments for the first time and describe a new genus and species for this suborder. Hausera Leal-Zanchet & Souza, gen. n. has features concordant with those defined for the family Dimarcusidae. The new genus is characterized by two unique features, viz. an intestine extending dorsally to the brain and ovovitelline ducts located dorsally to the nerve cords, which is complemented by a combination of other characters. The type-specimens of Hausera hauseri Leal-Zanchet & Souza, sp. n. are typical stygobionts, unpigmented and eyeless, and they may constitute an oceanic relict as is the case of other stygobiotic invertebrates found in this karst area in northeastern Brazil.